PO072 Does dbs surgery outcome affect patients use of outpatient resources?. (1st December 2017) - Hammersley, Beth; Lowry, Lindsey; Alusi, Sundus
Abstract : Deep brain stimulation (DBS) is carried out in our centre mainly for, Parkinson's disease, dystonia and tremor. Patients are seen by DBS nurses at baseline, 3, 6 and 12 months postoperatively; yearly thereafter. In between these times, patients have open access contact with the service which is largely outpatient (OP) led. However, trouble shooting also takes place over the phone and, when urgent, as ward attendance. We are under the impression that some patients use the service significantly more than others. However, it was not clear to us whether OP appointments rate varied across the conditions, or patients' surgical outcome. In this audit study we looked at whether higher follow up rate is seen in patients with worse surgical outcome in the three conditions. Disease specific outcome scores (>50%, 25%–50% and, <25% improvement) were correlated with number of times patients were seen in OP in year 1, 2 and 3. There was no significant difference in the number of times patients were seen across the groups. Our perception that poorer surgical outcome patients required more OP resources was not supported by this study. However, it is highly possible that patients' satisfaction plays a big role in their service use.